Using information policy tools for public governance in emergency situations - Dziundziuk, Viacheslav (Pressing Problems of Public Administration, 2024)
The article explores the unique aspects of leveraging information policy tools to ensure effective public administration during emergencies. Through an in-depth analysis of international practices in utilizing modern information and communication technologies to facilitate communication between authorities and citizens during crises–particularly in the United States, the United Kingdom, Poland, Germany, and Japan–the author identifies key principles and mechanisms for organizing information exchange under emergency conditions. The study delineates three critical phases of informational support during emergencies: (1) the preparation and early warning phase to alert the population about potential threats, (2) the operational response phase focused on mitigating the immediate impacts of the crisis, and (3) the recovery and normalization phase following the resolution of the emergency. The author emphasizes the vital importance of clearly defining roles and responsibilities among various government bodies in crisis communications, alongside the necessity of designating a central coordinating authority responsible for developing and implementing a comprehensive information policy. The article thoroughly examines the advantages and limitations of both traditional and modern channels and tools for information exchange, including official government websites, social media platforms, messaging applications, and specialized mobile apps. Based on the identified challenges in the interaction between public administration and the population during emergencies in Ukraine, the author proposes a set of priority measures to enhance effectiveness. These include the development and implementation of a national communication strategy for emergencies, strengthening interagency coordination and clarifying responsibilities, leveraging modern digital technologies more actively, and establishing high-quality, real-time feedback mechanisms with citizens. The conclusions underscore the necessity of developing a systemic national information policy as an essential component for improving crisis public administration, integrating global best practices with the unique realities of Ukraine. The results of the study can be used in the practical activities of public authorities to build effective crisis communication systems and increase public confidence in government actions during emergencies.